Echolocation, Art and Technology: interview with Marc Lee - Carneiro Paiva, José Wilker (Revista Vazantes, 2020)
Interview with the multimedia artist Marc Lee, where he spoke about one of his last works, Echolocation (2018), his ideas, interests and impressions about art and technology, addressed the technical aspects of the development of his works through open source tools and the interactive strategies he adopted to accomplish his work amid contemporary possibilities.